MU'TEZİLE KELAM SİSTEMİNDE ÖTEKi - Yüceer, İsa (Fırat University, 2006)
The philosophers were aware of what the original thoughts of Mu'tezile meant when they emerged as the school of Islamic theology. When the strong opposition was comibined by the public, hadis ehli, Hanbelis and Es'aris; Mu'tezile was in a bad situation and people had a bad opinion of him. When the other schools of Islamic Theology were added to this opposition Mu'tezile had problems to survive. Mu'tezile had also suffered from his relationships with the politicians. Despite the fact that he continued his presence among the school s of . Islamic Theology, he had problems to continue it on the public level. He had . achieved to build good relations with Zeydiye. Ehl-i Sunnet Resources made a merit of answering him and developed altematives against his thoughts.
Keywords: Religious Studies; Din Araştırmaları